A Framework for Developing Women Leaders: Applications to Executive Coaching. (June 2015) - O'Neil, Deborah A.; Hopkins, Margaret M.; Bilimoria, Diana
Informed by extant literature, we develop a framework of women's leadership development that integrates the key factors affecting women's leadership development (challenging organizational contexts, work–life integration and career/life-stage concerns) and the characteristics of women's leadership presence. We define leadership presence as a combination of a woman's unique voice, style of engagement, and positive contributions—composed of her self-confidence, self-efficacy, influence, and authenticity. We apply the framework to three composite executive coaching scenarios developed from our collective executive coaching experiences. The applications illustrate how a coach's guiding questions, focused on appropriate combinations of key factors and leadership presence developmental needs, can effectively facilitate women's leadership development. Practical implications for executive coaching practice as well as directions for future research are discussed.